2013
DOI: 10.1093/neuonc/not164
|View full text |Cite
|
Sign up to set email alerts
|

MiR-328 promotes glioma cell invasion via SFRP1-dependent Wnt-signaling activation

Abstract: Background Diffusely infiltrative growth of human astrocytic gliomas is one of the major obstacles to successful tumor therapy. Thorough insights into the molecules and pathways signaling glioma cell invasion thus appear of major relevance for the development of targeted and individualized therapies. By miRNA expression profiling of microdissected human tumor biopsy specimens we identified miR-328 as one of the main miRNAs upregulated in invading glioma cells in vivo and further investigated its role in glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 44 publications
3
65
0
1
Order By: Relevance
“…Because SLIT-2/ROBO1 signaling has been shown to suppress cell invasion by repressing Wnt/β-catenin signaling (through β-catenin) [18], we hypothesized that ROBO3 might exert its oncogenic effect in pancreatic cancer by up-regulating Wnt/β-catenin signaling. In several human cancers, the silencing of negative regulators of Wnt signaling, such as SFRP1, enhances tumor cell invasiveness [21][22][23][24][25]. SFRP was first identified as an antagonist of Wnt signaling and regulator of apoptosis [26] and is believed to function as an extracellular Wnt inhibitor [27].…”
Section: Discussionmentioning
confidence: 99%
“…Because SLIT-2/ROBO1 signaling has been shown to suppress cell invasion by repressing Wnt/β-catenin signaling (through β-catenin) [18], we hypothesized that ROBO3 might exert its oncogenic effect in pancreatic cancer by up-regulating Wnt/β-catenin signaling. In several human cancers, the silencing of negative regulators of Wnt signaling, such as SFRP1, enhances tumor cell invasiveness [21][22][23][24][25]. SFRP was first identified as an antagonist of Wnt signaling and regulator of apoptosis [26] and is believed to function as an extracellular Wnt inhibitor [27].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/beta-catenin signaling pathway is constitutively activated in glioma [13,14]; aberrant expression of betacatenin in astrocytic gliomas and glioblastoma is linked to a higher tumor grade [14]. SFRP1, a member of Wnt inhibitors, is an extracellular signaling molecule that directly binds Wnt ligands and antagonizes the Wnt signaling pathway, and silence of SFRP1 enhances tumorigenicity [7,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…SFRP1, a member of Wnt inhibitors, is an extracellular signaling molecule that directly binds Wnt ligands and antagonizes the Wnt signaling pathway, and silence of SFRP1 enhances tumorigenicity [7,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of miR-328-3p is found in many human tissues and has been shown to become de-regulated in different types of cancer [50], potentially affecting WNT-signaling via repression of the WNTinhibitor SFRP-1 [51]. Recently, it was shown that miR-328 targets the expression of CD44 in macrophages [52].…”
Section: Limitations Of the Studymentioning
confidence: 99%